Guidelines for Developing Mathematical Concepts and Strategies for Solving Mathematical Problems about Decimals and Fractions Using Non-Routine Problems for Mathayomsuksa 1 Students - Puttaldong, Thawisab; Nontapa, Navapon (NEU ACADEMIC AND RESEARCH JOURNAL, 2024)
This research aimed to (1) study mathematical concepts and problem-solving strategies using non-routine problems, (2) compare problem-solving strategies using unfamiliar problems categorized by conceptual groups, and (3) study guideline for develop mathematical concepts and problem-solving strategies. The population for this study includes 93 students from three classrooms from Mathayomsuksa 1 at Burapha Pittayakhom Municipal School in Maha Sarakham Province, during the second semester of the 2023 academic year. The sample consisted of 32 students from Mathayomsuksa 1/1, selected by cluster sampling. The research instruments included a test of mathematical concepts, a test of problem-solving strategies using non-routine problems, semi-structured interviews, and interviews for development approaches. The statistics used for data analysis were percentage, mean, standard deviation, task analysis, descriptive analysis, and content analysis. The research results showed that: (1) the majority of students have a low level of mathematical concepts, and in studying problem-solving strategies using unfamiliar problems, it was found that students most frequently chose the strategy of writing equations; (2) students with high and medium levels of concepts most frequently chose the strategy of writing equations; (3) in terms of development guidelines, teachers need to plan their teaching of decimals and fractions carefully, explaining slowly, teaching or explaining from simple to complex content, having students solve various types of problems, and using a variety of problem-solving strategies. Therefore, these guidelines can be used to further improve students' mathematical problem-solving skills.